2019
DOI: 10.1111/soc4.12678
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and the media: From illness to wellbeing

Abstract: The media are a main source of information about mental health for many people, and an ever‐growing body of literature is evaluating their coverage of the topic. To help keep track of such research, several comprehensive but now dated literature reviews have been published. We assess more recent studies (2007–2017) and suggest future directions by integrating (a) the “circuit of mass communication” model from media and communication studies which posits that production, content, and reception need to be analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 72 publications
(130 reference statements)
0
7
0
Order By: Relevance
“…Additionally, such confusion may also reflect society at large. As the term mental health has been increasingly used in media, it has often been used to depict instances of mental health issues rather than the spectrum of mental health or positive mental health (Atanasova et al, 2019). This is consistent with the uncertainty they expressed about positive mental health, sometimes relying more on an illness-based understanding.…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, such confusion may also reflect society at large. As the term mental health has been increasingly used in media, it has often been used to depict instances of mental health issues rather than the spectrum of mental health or positive mental health (Atanasova et al, 2019). This is consistent with the uncertainty they expressed about positive mental health, sometimes relying more on an illness-based understanding.…”
Section: Discussionmentioning
confidence: 87%
“…For this study, a thematic analysis of the shows Shadows, Going Downhill and Look at You has been attempted using Zygmunt Bauman's theory of liquid modernity. Several studies examine the personality traits of artists and the representation of mental health in literature and media using theories on psychology or communication (Atanasova et. al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Media coverage of mental health issues may either reinforce existing stigma or contribute to destigmatization (Atanasova et al, 2019; Goepfert et al, 2019; Sampogna et al, 2017; Sieff, 2003). Aragonès et al (2014) found in analyzing Spanish newspapers that 49% of the news items concerning mental issues linked mental disorders to danger like violent crimes which increases the perception of those affected as a threat.…”
Section: Pedophilia and Stigmamentioning
confidence: 99%